2011
DOI: 10.4236/ojo.2011.12003
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Lavage in Cementless Total Hip Arthroplasty Reduces the Incidence ofBrooker Grade 3 and 4 Heterotopic Ossifications

Abstract: Heterotopic ossification (HO) may cause pain, and can lead to loss of hip motion after total hip arthroplasty (THA). There is evidence that pulsed lavage may lower the incidence of HO formation. We assessed the effect of pulsed lavage on the incidence of HO in 87 male patients after THA. All patients received an uncemented THA through a posterolateral approach. 39 patients were treated with pulsed lavage (index group) and 48 males were treated without pulsed lavage (historical control group, matched on aetiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Sneath et al 26) have shown no difference in incidence of HO in their patient groups, in a randomized trial, despite use of pulsed lavage. But on the contrary, another prospective case control study by Mellema et al 27) has suggested a significant reduction in the incidence of severe grade HO with use of pulsed lavage. Unlike in our study they did not notice any improvement in the overall incidence between the groups (51% and 58%) but did notice a significant improvement in the severe grades (3% and 17%).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Sneath et al 26) have shown no difference in incidence of HO in their patient groups, in a randomized trial, despite use of pulsed lavage. But on the contrary, another prospective case control study by Mellema et al 27) has suggested a significant reduction in the incidence of severe grade HO with use of pulsed lavage. Unlike in our study they did not notice any improvement in the overall incidence between the groups (51% and 58%) but did notice a significant improvement in the severe grades (3% and 17%).…”
Section: Discussionmentioning
confidence: 91%
“…But we believe that if the lavage is done in a sequential manner, the debris are washed away as they are generated hence minimizing the risk of dissemination. There are only a handful of studies in literature which report the relation between formation of HO and use of pulsed lavage 26 27) . Sneath et al 26) have shown no difference in incidence of HO in their patient groups, in a randomized trial, despite use of pulsed lavage.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies[ 24 , 28 , 30 , 31 ] met the inclusion criteria and were included in the meta-analysis with 2 randomized controlled trials and 1 prospective non-randomized study, and 1 retrospective comparative study. It involved 185 subjects in the PL group and 182 subjects in the SL group.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed no difference in HO formation between PL and SL. A study by Mellema et al [ 28 ] showed a beneficial effect of PL in preventing Brooker grade 3-4 HO however this may be limited by the low numbers in such high HO grades. The etiology of this pathology is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation